Current Therapeutic Strategies in BRAF-Mutant Metastatic Colorectal Cancer - Grassi, Elisa; Corbelli, Jody; Papiani, Giorgio; Barbera, Maria Aurelia; Gazzaneo, Federica; Tamberi, Stefano (Frontiers in Oncology, 2021)
Around 8–12% of patients with advanced colon rectal cancer (CRC) present with BRAF alterations, in particular V600E mutation, which is associated with right-side, poorly differentiated and mucinous type tumors. The presence of BRAF mutation (BRAF-mt) has been identified as a hallmark of poor prognosis and treatment optimization in this patient subgroup is an important goal. Currently, the standard of care is an aggressive strategy involving triplet chemotherapy and anti-VEGF agents, but new therapeutic approaches are emerging. Very promising results have been obtained with targeted therapy combinations, such as anti-BRAF agents plus anti-EGFR agents. Furthermore, around 60% of BRAF-mt patients show a strong association with high microsatellite instability (MSI-H) and immune checkpoint inhibitors could represent the new standard of care for this subgroup. The focus of this review is to summarize current strategies for BRAF-mt CRC treatment and highlight new therapeutic options.